Implementasi Negative Word Of Mouth Terhadap Brand Image Bakso Pada Restoran Bakso Dono Dalam Perspektif Ekonomi Islam (Studi Kasus Konsumen Muslim Restoran Bakso Dono) - Marfuatul Khoiriah; Dendi Aswan Saputra (-, 2021)
This study aims to determine the effect of Negative Word of Mouth on the brand image of meatball products at Bakso Dono Restaurant. The research uses quantitative data. The sampling technique used is accidental sampling. Tests in this study were carried out by using convergent validity, reliability testing, and hypothesis testing using the Smart PLS 3 software. The data were obtained from distributing questionnaires using a Likert scale. The population is Bakso Dono restaurant consumers who are Muslim (Islam). With a sample of 50 respondents. The result is that negative word mouth has a positive and significant effect with the value of tstatistic ttable, which is 6.472 0.273.Keywords: Negative Word of Mouth, Brand Image, Islamic economic